Optimizing the synergy between stereotactic radiosurgery and immunotherapy for brain metastases - Yoo, Kelly H.; Park, David J.; Choi, John H.; Marianayagam, Neelan J.; Lim, Michael; Meola, Antonio; Chang, Steven D. (Frontiers in Oncology, 2023)
Solid tumors metastasizing to the brain are a frequent occurrence with an estimated incidence of approximately 30% of all cases. The longstanding conventional standard of care comprises surgical resection and whole-brain radiotherapy (WBRT); however, this approach is associated with limited long-term survival and local control outcomes. Consequently, stereotactic radiosurgery (SRS) has emerged as a potential alternative approach. The primary aim of SRS has been to improve long-term control rates. Nevertheless, rare observations of abscopal or out-of-field effects have sparked interest in the potential to elicit antitumor immunity via the administration of high-dose radiation.The blood-brain barrier (BBB) has traditionally posed a significant challenge to the efficacy of systemic therapy in managing intracranial metastasis. However, recent insights into the immune-brain interface and the development of immunotherapeutic agents have shown promise in preclinical and early-phase clinical trials. Researchers have investigated combining immunotherapy with SRS to enhance treatment outcomes in patients with brain metastasis.The combination approach aims to optimize long-term control and overall survival (OS) outcomes by leveraging the synergistic effects of both therapies. Initial findings have been encouraging in the management of various intracranial metastases, while further studies are required to determine the optimal order of administration, radiation doses, and fractionation regimens that have the potential for the best tumor response.Currently, several clinical trials are underway to assess the safety and efficacy of administering immunotherapeutic agents concurrently or consecutively with SRS. In this review, we conduct a comprehensive analysis of the advantages and drawbacks of integrating immunotherapy into conventional SRS protocols for the treatment of intracranial metastasis.